Design features of implants for direct skeletal attachment of limb prostheses. Issue 11 (2nd April 2013) - Pitkin, M.
<x xml:space="preserve">Abstract</x> In direct skeletal attachment (DSA) of limb prostheses, a construct is implanted into an amputee's residuum bone and protrudes out of the residuum's skin. This technology represents an alternative to traditional suspension of prostheses via various socket systems, with clear indications when the sockets cannot be properly fitted. Contemporary DSA was invented in the 1990s, and several implant systems have been introduced since then. The current review is intended to compare the design features of implants for DSA whose use in humans or in animal studies has been reported in the literature. © 2013 Wiley Periodicals, Inc. J Biomed Mater ResPart A: 101A: 3339–3348, 2013.